Precision medicines for B‐cell leukaemias and lymphomas; progress and potential pitfalls. (24th January 2013) - Dyer, Martin J. S.; Vogler, Meike; Samuel, Jesvin; Jayne, Sandrine; Wagner, Simon; Pritchard, Catrin; Macip, Salvador
Summary There is now a plethora of new precision medicines for B‐cell malignancy including 'classical' kinase inhibitors, rationally designed inhibitors of anti‐apoptotic proteins and antibody or antibody drug/toxin conjugates with functional properties. Some are showing spectacular single agent activity in early phase clinical studies and may reduce or, in combination, even obviate the need for chemotherapy. Nevertheless, significant problems remain if these medicines are to be introduced into routine clinical practice in a rational and affordable manner. Firstly, precision medicines must be carefully matched in a mechanistic fashion with specific subtypes of disease. Whilst sensitivity may be predicted by the detection of key mutations or by expression of target molecules, for therapies that depend on intact intracellular signalling pathways, functional assessment on viable primary malignant cells will be necessary using assays that faithfully mimic in vivo conditions. A second, but no less important challenge is to define mechanism‐based synergistic combinations associated with minimal toxicities rather than simply adding new precision medicines to existing chemotherapeutic regimens. Finally, a closer, open, two‐way interaction between academic medicine and the pharmaceutical industry will be necessary to achieve these aims. Implementing such changes would change radically how and where patients with B‐cell malignancies are managed.